Development and Characterization of a Polycaprolactone/Graphene Oxide Scaffold for Meniscus Cartilage Regeneration Using 3D Bioprinting - Ozder, Melike Nur; Yelkenci, Aslihan; Kucak, Mine; Altinbay, Aylin; Ustundag, Cem Bulent; Ciftci, Fatih (MDPI, 2025)
Highlights GO increased the storage modulus of scaffolds from 36.1 Pa to 97.1 Pa. Yield shear stress enhanced from 97.2 Pa to 507.1 Pa with GO. Optimal mechanical properties achieved with 1% GO: modulus 614 MPa and strength 46.3 MPa. GO incorporation increased the melting temperature to 60.78 degrees C and glass transition to 31.14 degrees C. Roughened scaffold surface improved cell adhesion and cellular distribution confirmed by DAPI staining. Antibacterial zones increased against (26.21 mm) and (15.38 mm). E. coliS. aureusRheological results showed shear-thinning viscosity improvement up to 89.3 Pas with GO. Elongation at break improved to 10.4% with 5% GO addition. GO scaffolds enhanced cell viability to over 100% at 1:8 concentration. PCL/GO scaffolds successfully mimicked native meniscus properties with biofunctional and mechanical advantages.Abstract Background/Objectives: Meniscus injuries represent a critical challenge in orthopedic medicine due to the limited self-healing capacity of the tissue. This study presents the development and characterization of polycaprolactone/graphene oxide (PCL/GO) scaffolds fabricated using 3D bioprinting technology for meniscus cartilage regeneration. Methods: GO was incorporated at varying concentrations (1%, 3%, 5% w/w) to enhance the bioactivity, mechanical, thermal, and rheological properties of PCL scaffolds. Results: Rheological analyses revealed that GO significantly improved the storage modulus (G') from 36.1 Pa to 97.1 Pa and the yield shear stress from 97.2 Pa to 507.1 Pa, demonstrating enhanced elasticity and flow resistance. Mechanical testing showed that scaffolds with 1% GO achieved an optimal balance, with an elastic modulus of 614 MPa and ultimate tensile strength of 46.3 MPa, closely mimicking the native meniscus's mechanical behavior. FTIR analysis confirmed the successful integration of GO into the PCL matrix without disrupting its chemical integrity, while DSC analysis indicated improved thermal stability, with increases in melting temperatures. SEM analysis demonstrated a roughened surface morphology conducive to cellular adhesion and proliferation. Fluorescence microscopy using DAPI staining revealed enhanced cell attachment and regular nuclear distribution on PCL/GO scaffolds, particularly at lower GO concentrations. Antibacterial assays exhibited larger inhibition zones against E. coli and S. aureus, while cytotoxicity tests confirmed the biocompatibility of the PCL/GO scaffolds with fibroblast cells. Conclusions: This study highlights the potential of PCL/GO 3D-printed scaffolds as biofunctional platforms for meniscus tissue engineering, combining favorable mechanical, rheological, biological, and antibacterial properties.
Keywords: 3D bioprinting; graphene oxide; meniscus scaffolds; cartilage; PCL; REDUCED GRAPHENE OXIDE; HYDROGEL; DEGRADATION; Pharmacology & Pharmacy